Factors associated with mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in sub-Saharan Africa: a multilevel robust Poisson regression modelling - Getayeneh Antehunegn Tesema; Beminate Lemma Seifu (BMC, 2023)
Abstract Background Timely and appropriate treatment for childhood illness saves the lives of millions of children. In low-middle-income countries such as sub-Saharan Africa (SSA), poor healthcare-seeking behavior for childhood illnesses is identified as a major contributor to the increased risk of child morbidity and mortality. However, studies are limited on Factors associated with mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in sub-Saharan Africa. Objective To examine factors associated with a mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in sub-Saharan Africa. Methods A secondary data analysis was conducted based on the latest Demographic and Health Survey (DHS) data of 36 sub-Saharan African countries. A total weighted sample of 16,925 mothers who had under-five children with acute respiratory infection symptoms was considered. The Intraclass Correlation Coefficient (ICC), Median Odds Ratio (MOR), and Likelihood Ratio (LR) tests were done to assess the presence of clustering. Model comparison was made based on deviance (-2LLR) value. Variables with a p-value < 0.2 in the bivariable multilevel robust Poisson analysis were considered for the multivariable analysis. In the multivariable multilevel robust Poisson regression analysis, the Adjusted Prevalence Ratio (APR) with the 95% Confidence Interval (CI) was reported to declare the statistical significance and strength of the association. Results The prevalence of mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in SSA was 64.9% (95% CI: 64.2%, 65.7%). In the multivariable analysis; mothers who attained primary education (APR = 1.11, 95% CI: 1.08, 1.15), secondary education (APR = 1.13, 95% CI: 1.09, 1.18), and higher education (APR = 1.19, 95% CI: 1.11, 1.27), belonged to the richest household (APR = 1.07: 95% CI: 1.02, 1.12), had media exposure (APR = 1.11, 95% CI: 1.08, 1.15), currently working (APR = 1.08, 95% CI: 1.06, 1.11), had ANC use (APR = 1.25: 95% CI: 1.17, 1.35), health facility delivery (APR = 1.10, 95% CI: 1.07, 1.14), belonged to West Africa (APR = 1.04, 95% CI: 1.01, 1.08) and being in the community with high media exposure (APR = 1.04, 95% CI: 1.02, 1,07) were significantly associated with higher prevalence of mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children. On the other hand, distance to a health facility (APR = 0.87, 95% CI: 0.84, 0.91), and being in central Africa (APR = 0.87, 95% CI: 0.84, 0.91) were significantly associated with a lower prevalence of mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children. Conclusion Mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children. It was influenced by maternal education, maternal working status, media exposure, household wealth status, distance to the health facility, and maternal health care service use. Any interventions aiming at improving maternal education, maternal healthcare services, and media access are critical in improving mothers' healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children, hence lowering the prevalence of ARI-related death and morbidity.